Environmental policy and administration in India: Role of government, Parliament and Supreme Court - Bava, Noorjahan (2004)
Industrial development and urbanisation have taken a heavy toll of environment and ecology. Coupled with the unprecedented pressure of population explosion on natural resources, the detrimental effects of unregulated and rapacious development activities have made it imperative for the state and its agencies to intervene in order to save people and their environment from the resultant ill-effects. This article gives an extensive account of regulatory interventions that have been effected through various legislations and court verdicts. It elaborates upon the environmental law principles which are based on interpretation of Constitution and statues, combined with a liberal view ensuring social justice and human rights. Following these principles the courts have sometimes emphasised environment over development when the situation demanded an immediate and specific policy structure. - Reproduced.
Keywords: Public administration - India; Environmental policy - India; Environmental policy